2019
DOI: 10.3748/wjg.v25.i40.6063
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like growth factor 2 mRNA-binding protein 1 promotes cell proliferation via activation of AKT and is directly targeted by microRNA-494 in pancreatic cancer

Abstract: BACKGROUNDStudies have shown that insulin-like growth factor 2 mRNA-binding protein 1 (IGF2BP1) plays critical roles in the genesis and development of human cancers.AIMTo investigate the clinical significance and role of IGF2BP1 in pancreatic cancer.METHODSExpression levels of IGF2BP1 and microRNA-494 (miR-494) were mined based on Gene Expression Omnibus datasets and validated in both clinical samples and cell lines by quantitative real-time polymerase chain reaction and Western blot. The relationship between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 23 publications
1
38
0
Order By: Relevance
“…For this study, we focused on the PoRs (Figure 3A), since these represent factors that may promote dedifferentiation and diseases progression and may thus present therapeutic targets eligible for treatment by inhibition, as proposed for LIN28B [29] and other RBPs. Among the 44 PoRs were proteins previously implicated in PDAC progression, e.g., IGF2BP1-3 [13][14][15][16][17], IFIT3 [30], EXO1 [21], or PTBP3 [23]. However, there were also proteins that, to the best of our knowledge, have not yet been associated with oncogenic potential in pancreatic cancer, e.g., OAS proteins, RBM34 or DQX1.…”
Section: Transcriptional Regulation Of Rbps In Pdacmentioning
confidence: 96%
See 1 more Smart Citation
“…For this study, we focused on the PoRs (Figure 3A), since these represent factors that may promote dedifferentiation and diseases progression and may thus present therapeutic targets eligible for treatment by inhibition, as proposed for LIN28B [29] and other RBPs. Among the 44 PoRs were proteins previously implicated in PDAC progression, e.g., IGF2BP1-3 [13][14][15][16][17], IFIT3 [30], EXO1 [21], or PTBP3 [23]. However, there were also proteins that, to the best of our knowledge, have not yet been associated with oncogenic potential in pancreatic cancer, e.g., OAS proteins, RBM34 or DQX1.…”
Section: Transcriptional Regulation Of Rbps In Pdacmentioning
confidence: 96%
“…Despite the lack of systematic investigation of RBPs in PDAC, ample evidence suggests substantial impact of some RBPs in this malignancy. For example, all three members of the insulin-like growth factor 2 mRNA binding protein family (IGF2BPs) have recently been described as being upregulated and associated with a poor prognosis in pancreatic cancer [13][14][15][16][17]. Furthermore, inactivation of the histone deacetylase SIRT6 was reported to accelerate PDAC progression in mouse models due to upregulation of LIN28B [18].…”
Section: Introductionmentioning
confidence: 99%
“…By binding different mRNAs, IGF2BPs decide the fate of those mRNAs by controlling their localization, stability, and translation [40]. Many studies have reported the role of IGF2BPs in cell proliferation, cell invasion, tumorigenesis, and embryogenesis [40][41][42][43][44][45][46][47][48][49][50][51]. IGF2BPs have also been found in sheep trophoblast cells suggesting their role in rapid proliferation of these cells [52].…”
Section: Introductionmentioning
confidence: 99%
“…First, IGF2BP1 (insulin-like growth factor 2 mRNA binding protein 1) plays significant roles in carcinogenesis, including tumor cell proliferation and growth, invasion, and chemoresistance, and is associated with poor overall survival and metastasis in various types of human cancers [30]. This gene was also reported to be upregulated and associated with a poor prognosis in pancreatic cancer patients [31]. It inhibits pancreatic cancer cell growth in vitro and in vivo via the AKT signaling pathway.…”
Section: Discussionmentioning
confidence: 99%